The complete mitochondrial genome of Myrmeleon formicarius (Neuroptera: Myrmeleontidae) - Jieqin Wu; Shaozhen Wang; Xiaozhen Yang; Yajie Guo; Xiaoqian Weng; Songqing Wu (Mitochondrial DNA. Part B. Resources, 2020)
In this study, the first complete mitochondrial genome of Myrmeleon formicarius was sequenced. The length of the complete mitochondrial genome of M. formicarius was 16,179 bp with 25.19% GC content. There were 13 protein-coding genes (CDS), 22 transfer RNA genes (tRNA), two ribosomal RNA genes (rRNA), and an AT-rich region. Phylogenetic analysis showed that M. formicarius was closely related to M. immanis. This study provides useful genetic information to better understand the genetic evolution of Myrmeleontidae.